EBV-1 and HCMV in aggressive periodontitis in Brazilian patients EBV-1 e HCMV na periodontite agressiva em pacientes brasileiros - Soraia Almeida Watanabe; Jeane de Fátima Correia-Silva; Martinho Campolina Rebello Horta; José Eustáquio da Costa; Ricardo Santiago Gomez (Sociedade Brasileira de Pesquisa Odontológica, 2007)
The purpose of the present investigation was to compare the presence of Epstein-Barr virus type 1 (EBV-1) and of Human Cytomegalovirus (HCMV) in crevicular fluid samples from deep and shallow periodontal pocket sites of Brazilian patients with aggressive periodontitis. A total of 30 systemically healthy patients with aggressive periodontitis participated in the study. Paper points were inserted into 2 gingivitis sites (< 3 mm) and into 2 periodontitis sites (> 5 mm) in each patient. PCR assay was used to identify genomic copies of HCMV and EBV-1. Twenty-three patients (77%) were positive for EBV-1, while only 2 patients (6%) were positive for HCMV. The McNemar test revealed a positive association between EBV-1 and periodontal lesions (p = 0.043). Thirty-four (57%) out of 60 periodontitis sites were positive for EBV-1, whereas 18 (30%) gingivitis sites were positive (p = 0.01). Only two sites (6.7%) were positive for HCMV. No positive association was found between HCMV and periodontitis or gingivitis (p = 0.479). The elevated occurrence of EBV-1 DNA in periodontal pockets of patients with aggressive periodontitis supports a possible periodontopathic role of this virus. O objetivo do presente estudo foi comparar a presença do vírus Epstein-Barr tipo 1 (EBV-1) e do Citomegalovírus Humano (HCMV) em amostras de fluido crevicular de bolsas periodontais rasas e profundas de pacientes brasileiros com periodontite agressiva. Trinta pacientes sistemicamente saudáveis com periodontite agressiva participaram deste estudo. Cones de papel foram inseridos em 2 sítios de gengivite (< 3 mm) e em 2 sítios de periodontite (> 5 mm) de cada paciente. Reações de PCR foram usadas para identificar cópias de DNA genômico de HCMV e EBV-1. Em 23 pacientes (77%), os testes foram positivos para EBV-1, enquanto apenas 2 pacientes (6%) foram positivos para HCMV. O teste de McNemar apontou associação positiva entre EBV-1 e lesões periodontais (p = 0,043). Trinta e quatro (57%) dos 60 sítios de periodontites foram positivos para o EBV-1, enquanto 18 (30%) dos sítios de gengivites foram positivos (p = 0,01). Apenas 2 sítios (6,7%) foram positivos para o HCMV. Não foi encontrada associação positiva entre HCMV e periodontite ou gengivite (p = 0,479). A alta ocorrência de DNA de EBV-1 em bolsas periodontais de pacientes com periodontite agressiva corrobora a possível função periodontopática deste vírus.